2008
DOI: 10.2137/145960611797215691
|View full text |Cite
|
Sign up to set email alerts
|

Effects of grass-red clover silage digestibility and concentrate protein concentration on performance, carcass value, eating quality and economy of finishing Hereford bulls reared in cold conditions

Abstract: The aim of the present experiment was to study the effects of (1) digestibility of grass-red clover silage (GCS) and (2) concentrate protein concentration on the performance, eating quality and economy of Hereford bulls during a six months pre-slaughter period, and reared in cold indoor facilities. Thirty-one bulls with an initial live weight (LW) of 289 kg were selected for a 2 × 2 factorial design experiment consisting of two primary growth GCSs harvested at different maturities (in vitro digestible organic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
12
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 35 publications
9
12
1
Order By: Relevance
“…In the groundnut cake supplemented groups perform better than other groups in body length and height. This agrees with [16] that the intake of tropical grass may decline remarked ably when crude protein percentage goes below 6%. This leads to sub-optimum level of nitrogen for the rumen flora, which requires an increase in the amount of feed ingested for improvement of animal performance when grazing such forages to maintain better performance [17].…”
Section: Discussionsupporting
confidence: 91%
“…In the groundnut cake supplemented groups perform better than other groups in body length and height. This agrees with [16] that the intake of tropical grass may decline remarked ably when crude protein percentage goes below 6%. This leads to sub-optimum level of nitrogen for the rumen flora, which requires an increase in the amount of feed ingested for improvement of animal performance when grazing such forages to maintain better performance [17].…”
Section: Discussionsupporting
confidence: 91%
“…Previous reports have shown no effects of silage digestibility on dressing proportion, carcass conformation and fat scores (Steen 1988b, Cummins et al 2007, Manninen et al 2011). However, increasing energy intake has often increased carcass conformation (Aronen et al 1994, Caplis et al 2005, Pesonen et al 2013, Huuskonen and Huhtanen 2015 and carcass fatness (Huuskonen et al 2007, Pesonen et al 2013, Huuskonen and Huhtanen 2015, Manni et al 2016 of growing and finishing cattle but these effects could not be demonstrated in the present experiment.…”
Section: Discussionmentioning
confidence: 90%
“…It can be assumed that the main reason for the high growth rate was the effect of high silage digestibility leading to high energy intake. Earlier, also Manninen et al (2011) ) when finishing Hereford bulls were fed highly digestible silage (D values 750 and 699 g kg -1 DM, respectively) and barley-based concentrate supplementation. The improved growth rate on highly digestible silage has previously been confirmed in several studies (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to above-mentioned variables this dataset included also information of commercial cuttings. Each carcass was cut into valuable cuts: outside round (Musculus semitendinosus), inside round (Musculus semimembranosus), corner round (Musculus quadriceps femoris), roast beef (Musculus gluteus medius), tenderloin (Musculus psoas major) and loin (Musculus longissimus) and subcutaneous fat as described by Manninen et al (2011) and Pesonen et al (2012). All these cuttings were weighed automatically in line and their yields were expressed as percentages of the carcass cold weight (0.98 × carcass hot weight, 50 min post-mortem).…”
Section: Dataset -Commercial Cuttingmentioning
confidence: 99%